Serum levels of insulin-like growth factor-1 and brain-derived neurotrophic factor as potential recovery biomarkers in stroke. (3rd April 2019) - King, Michael; Kelly, Liam P.; Wallack, Elizabeth M.; Hasan, S. M. Mahmudul; Kirkland, Megan C.; Curtis, Marie E.; Chatterjee, Tanaya; McCarthy, Jason; Ploughman, Michelle
ABSTRACT: Objectives : Our objectives were: 1) to determine whether maximal aerobic exercise increased serum neurotrophins in chronic stroke and 2) to determine the factors that predict resting and exercise-dependent levels. Methods : We investigated the potential predictors of resting and exercise-dependent serum insulin-like growth factor-1 and brain-derived neurotrophic factor among 35 chronic stroke patients. Predictors from three domains (demographic, disease burden, and cardiometabolic) were entered into 4 separate stepwise linear regression models with outcome variables: resting insulin-like growth factor, resting brain-derived neurotrophic factor, exercise-dependent change in insulin-like growth factor, and exercise-dependent change brain-derived neurotrophic factor. Results : Insulin-like growth factor decreased after exercise (p = 0.001) while brain-derived neurotrophic factor did not change (p = 0.38). Greater lower extremity impairment predicted higher resting brain-derived neurotrophic factor (p = 0.004, r 2  = 0.23). Higher fluid intelligence predicted greater brain-derived neurotrophic factor response to exercise (p = 0.01, r 2  = 0.18). There were no significant predictors of resting or percent change insulin-like growth factor-1. Discussion : Biomarkers have the potential to characterize an individual's potential for recovery from stroke. Neurotrophins such as insulin-like growth factor-1 and brain-derived neurotrophic factor are thought to be important in neurorehabilitation; however, the factors that modulate these biomarkers are not well understood. Resting brain-derived neurotrophic factor and percent change in brain-derived neurotrophic factor were related to physical and cognitive recovery in chronic stroke, albeit weakly. Insulin-like growth factor-1 was not an informative biomarker among chronic stroke patients. The novel finding that fluid intelligence positively correlated with exercise-induced change in brain-derived neurotrophic factor warrants further research.